The Effects of Fasting-Induced Skeletal Muscle Remodelling on PRMT Biology and Regulation of Cellular and Molecular Processes in Human Skeletal Muscle - Raziee, Rozhin (My University, 2024)
Protein arginine methyltransferases (PRMTs) are enzymes that catalyze the addition of methyl groups onto arginine residues of target proteins, thereby altering their activity. PRMTs have recently emerged as mediators of skeletal muscle biology in health and disease. However, the role of PRMTs in response to nutritional cues for muscle remodelling in humans remains unclear. In addition, molecular and cellular changes in skeletal muscle following 48 hours of fasting have not yet been elucidated. Thus, the purpose of this study is to investigate PRMT biology during conditions of fasting-induced skeletal muscle plasticity as well as to explore changes to atrophy-, autophagy-, and muscle protein synthesis (MPS)-related pathways in response to nutrient deprivation. Muscle biopsies were collected from the vastus lateralis of ten healthy men (22.0 yrs ± 1.5) prior to and after a 48-hour fast. Our data demonstrate that fasting modestly decreased muscle cross-sectional area in type II fibers, and elicited a significant shift toward more oxidative type I fibers. Additionally, fasting diminished global arginine methylation in the muscle while protein and mRNA levels of PRMTs remained relatively stable. In this study, the autophagy markers explored were diminished or remained unchanged, and muscle protein breakdown signalling was initiated via increased mRNA levels of muscle atrophy F-box (MAFbx). Lastly, we observed significant decreases in the phosphorylation status of canonical MPS markers, accompanied by a significantly increased translocation of mammalian target of rapamycin (mTOR) to the cell periphery. Collectively, this study provides insight into the regulation of skeletal muscle signalling and protein arginine methylation in response to nutrient and energy deficits in humans.